PENGARUH BOARD STRUCTURE TERHADAP VALUE RELEVANCE OF ACCOUNTING INFORMATION MELALUI INTELLECTUAL CAPITAL DISCLOSURE SEBAGAI VARIABEL MEDIASI - Carine Jacqueline Hetharie; Saarce Elsye Hatane (Business Accounting Review, 2018)
This study aimed to examine the direct and significant influence between board structure on value relevance of accounting information. Also this study examine indirect influence between board structure to value relevance of accounting information through intellectual capital disclosure as the mediating variable. The sample used in this study were 41 banks listed on Indonesia Stock Exchange starting from 2011-2016. The data processed by using WarpPLS software version 5.0.The result of this research found the positive effect of board structure on intellectual capital disclosure, the positive effect of board structure on value relevance of accounting information, the positive effect of intellectual capital disclosure on value relevance of accounting information. Intellectual capital disclosure successfully mediates the influence of board structure on value relevance of accounting information.